Assessment and Analysis of Sustainability Status in Metropolises, Case Study: All Ten Regions of Tabriz - Alireza Soleimani; Ali Majnouni Toutakhane; Ali Reza Soleimani; Ahmad Aftab (تحقيقات جغرافيايی, 2018)
Urban development based on the principles of sustainable development has been one of the main concepts of urbanization in the last decade. The term sustainable urban development means providing the necessary grounds for the balanced and efficient utilization of urban resources so that all citizens can benefit from urban economic, social and environmental infrastructure in accordance with their needs. The aim of this research is to investigate the sustainability status in Tabriz metropolis. This is a descriptive-analytic research. The statistical population of this research is the inhabitants of all ten regions of Tabriz, and 500 individuals over 15 years old are selected as sample size using simple random sampling by the classified method. The validity of the questionnaire was verified by experts and the reliability of the different parts of the questionnaire obtained the score of 0.876 to 0.881 using Cronbachchr('39')s alpha coefficient. Fuzzy TOPSIS Method is used to evaluate the variables in order to assess the sustainability, the model of barometer sustainability is used. Also to infer and testability of data the statistical tests such as Anova test, T test and Tukey and Scheffe tests are used. Drawing of maps related to the stability of Tabriz urban areas has been done using GIS software. According to the results, region 8 is the most sustainable region and region 3 is the most unstable region. Also, all 10 regions of Tabriz with sustainability value of 0.591 are in medium sustainability status. The status of the regions in terms of human welfare and ecosystem well-being was also equal to 0.548 and 0.515 respectively. The results of T and Anova tests also showed that according to the sustainability barometric results, physical, social, economic and environmental dimensions are of the most importance respectively. Tukey and Scheffe tests also demonstrated the stability gap between different dimensions of sustainability. Finally, according to the findings of the research and taking into account the situation of the tens of ten regions of Tabriz, practical suggestions are presented in accordance with different dimensions of sustainable urban development.